A Brief Review of Ruta Graveolens plant in Homoeopathic System of Medicine - Deepti Sharma (Indian Journal of Integrative Medicine, 2022)
Ruta Graveolens is an odoriferous and evergreen herb belonging to the family Rutaceae. The plant, also known as bitter herb or common rue, is grown in gardens all over the world and is used in the homeopathic medical system. In this article, the introduction of the plant, morphological study, systematic position, and phytochemistry of the Ruta Graveolens is discussed. It has bluish leaves and is grown as ornamental. It is also cultivated as a medicinal herb, a spice, and sometimes, as an insect repellent. The plant grows in hot and dry soil conditions. For a prolonged duration, R. Graveolens has traditionally been used for the relief of pain, eye and skin complaints, and rheumatism. R. Graveolens also shows antihysterical, ophthalmic, antihelminthic, antiepileptic, antihelminthic, miscarriage, and convulsive effects.